Systematic Literature Review: Design of Mathematics Modules Based on Ethnomathematics - Ababil, Dini; Purwasi, Lucy Asri; Nugroho, Khathibul Umam Zaid (Global Education Journal, 2025)
Amidst the onslaught of globalization in the 21st century, education must innovate in learning to develop problem-solving skills and foster a love of local culture. One way to do this is through the implementation of ethnomathematics in learning. The purpose of this study is to describe the implementation of ethnomathematics in learning to develop mathematical problem-solving skills and a love of local culture. The study used the Systematic Literature Review (SLR) method for articles published between 2018 and 2023 on the impact of ethnomathematics on mathematical problem-solving skills and a love of local culture. Fourteen national and international articles were obtained from the Google Scholar and Scopus databases. The results indicate that ethnomathematics learning can effectively help develop students' problem-solving skills and a love of local culture. Its implementation is used as an integrated approach in learning models and learning media. Therefore, the design of ethnomathematics-based mathematics modules has greater potential to improve students' understanding of mathematical concepts and learning motivation from various cultural backgrounds.